1999
DOI: 10.1177/205873929901200204
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Dependent Killing of Mycobacterium Tuberculosis by Human Mononuclear Phagocytes from Patients with Active Tuberculosis

Abstract: In this study we have demonstrated that nitric oxide, the product of the arginine dependent pathway of human mononuclear phagocytes effectively kills the M.tuberculosis in-vitro. The release of reactive nitrogen intermediates was triggered by incubation with various proinflammatory cytokines namely IFN gamma,TNF-alpha and IL-1 R. We have earlier shown that human mononuclear phagocytes can be induced to release nitric,oxide (NO) radicals which can kill tumour cells. In the present communication, by using colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…It was necessary to stimulate the alveolar epithelial cells by cytokines to bring down the CFU (Table 2). Our results confirm earlier reports 4,27 that cytokine mixture leads to release of very high concentration of NO. We further demonstrated that the reduction in CFU occurred in the same wells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was necessary to stimulate the alveolar epithelial cells by cytokines to bring down the CFU (Table 2). Our results confirm earlier reports 4,27 that cytokine mixture leads to release of very high concentration of NO. We further demonstrated that the reduction in CFU occurred in the same wells.…”
Section: Discussionsupporting
confidence: 93%
“…The pellet was resuspended in DMEM supplemented with 10% FCS and passed through an 8‐µm filter to prepare a single cell suspension. The dispersed bacterial concentration was measured by taking absorbance at 600 nm using MacFarland's nephelometric standards 27 . The bacterial concentration was adjusted to a density of 10 8 bacteria/ml, aliquoted and kept as a single lot at 4°.…”
Section: Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Bose et al demonstrated that in a murine TB model NO production played an essential role in Mtb killing by mononuclear phagocytes, particularly during the early phase of the infection. Additionally, it may also play a role in tissue damage during the late phases of the disease [88]. In vitro studies using A549 cells showed an induction of NO in response to Mtb infection, which is consistent with the finding that NO has antimicrobial effects against Mtb infection [89].…”
Section: Airway Epithelial Cells and Their Host Defensessupporting
confidence: 72%
“…Interestingly enough, NO secretion by human macrophages is enhanced when alveolar macrophages are obtained from patients with lung injury, chronic lung inflammation [3] or patients with tuberculosis [44,45]. In the latter case, killing of mycobacteria in vitro by these macrophages was inhibited by NO inhibitors, thus indicating an antimicrobial role for NO, possibly also in humans during mycobacterial infection [46]. Currently, the mouse is an often-used animal model for the study of tuberculosis, and whether the differences in the antibacterial properties of human and mouse macrophages are relevant to study outcomes in the mouse has not been determined.…”
Section: Discussionmentioning
confidence: 99%